PENERAPAN METODE SIMPLE MULTI ATTRIBUTE RATING PADA APLIKASI PEMILIHAN VARIETAS BENIH PADI (STUDI KASUS PT. SANG HYANG SERI PALEMBANG) - Messakh, Darwin (TRANSFORMASI, 2023)
This Final Project aims to create an application using the Simple Multi Attribute Rating Technique (SMART) method that can help customers or farmers in choosing rice seed varieties that suit their needs. This research is focused on a case study at PT Sang Hyang Seri Palembang. Using the SMART method is one of the effective approaches in overcoming decision making that carries several criteria or attributes. In the context of selecting rice seed varieties, there are several important criteria that need to be considered, such as production yield, resistance to pests, harvest period, and others. By applying the SMART method, it is expected that customers or farmers can be easier and more efficient in determining rice seed varieties. This research also uses a software development method that includes the stages of needs analysis, interface design, application implementation, and testing. The data used in this study were obtained from primary sources through surveys and interviews with employees at PT Sang Hyang Seri. This application will provide recommendations based on ranking values calculated from each criterion. Hopefully, this application will provide significant benefits for farmers in increasing rice production and the efficiency of their farming business.Â Keywords: Simple Multi Attribute Rating, Rice Seed Variety Selection, Application, Farmer, PT Sang Hyang Seri.